ANALISIS KINERJA PROSES PRODUKSI PLASTIK ROLL POLYPROPYLENE MENGGUNAKAN METODE SIX SIGMA PADA PT KUSUMA MULIA PLASINDO INFITEX - Fathurahman Muhammad; Ari Zaqi Al Faritsy (CV. KAMPUS AKADEMIK PUBLISING, 2026)
In the production process of polypropylene (PP) plastic, defective products were found in the form of stubble and wrinkle with a percentage of 1.50% and 1.12% wrinkle defect. Six Sigma was employed as the analytical method in this study, utilizing DMAIC framework (Define, Measure, Analyze, Improve, and Control). This research was designed to determine sigma level, examine factors responsible for product defects, and propose corrective actions aimed at reducing defective outputs. The analysis produced a sigma value of 3.74, where defects were found to originate from three main sources: machinery issues caused by damaged heating components, human-related errors due to insufficient accuracy and lack of supervision during production, and environmental conditions such as dust and elevated production room temperatures that influence workers’ psychological state.